Koraközépkori hagiográfia és a kopt irodalom. Egy kopt osztrakon szövegének irodalomtörténeti elemzése - Tóth, P (ELTE Egyetemi Könyvtár, 2001)
This paper examines a text of a Coptic ostracon which contains a debate between the fourteen-year old Saint Cyrill of Alexandria and some pagan greek philosophers. Saint Cyrill († 444) was the patriarch of Alexandria between 412–444 and was one of the most significant figures of universal Christianity. He was a great theologian and defended orthodoxy against heretic teaching especially Nestorianism. His attack on Nestorios lead to the III. Ecumenical Council of Ephesus in 431, where Cyrill's dogmas were accepted and it was stated that Christ is perfect God and perfect human being, and in him the two natures constitute an unmingled unity. Despite the fact that Cyrill was the patriarch of Alexandria, the capital city of Egypt, most of his works, as it is usual among the bishops of Egypt, survive in Greek. A Copto-Egyptian tradition, however, concerning his person can be reconstructed in the form of some pieces and fragments. Such piece is the limestone ostracon of The Museum of Berlin. The examination of this text tries to point out the role of national literary traditions in Late Antique Mediterranean forming the literary character of such a significant theologian in the life of the local church. Finding and examining literary, especially hagiographical parallels of the text draw light on the most important features of Coptic tradition concerning the greatest church fathers of Egypt. Investigating other traditions concerning the person of Cyrill, we find that only the fragmentary Coptic tradition contains such an emphasising of the spiritual and secular wisdom of the patriarch. The literary form of the text bears witness to the same. Trying to find comparison to the genre of the Coptic text, we see that beside apocryphal stories on the debates of the twelve-year old Jesus Christ with the Jews (which always makes base for compiling such stories) especially one kind of Martyr-stories can be compared with text. The genre of the so-called apologetic passions also contains theological-philosophical debates between the martyr and the prefect. Therefore, in our view, this kind of Martyr-Acts were the literary device to express the above referred idea of praising the wisdom of the church fathers. What could, however, be the purpose of this idea? After the schism of Coptic Christianity the local church tries to prove its orthodoxy towards the Byzantine Oecumene by asserting the adherence to the teaching of the patriarchs of Alexandria, first of all Athanasius the Great and Cyrill of Alexandria. The form of emphasizing this adherence is writing theological treatises against Byzantine Church, but even more compiling hagiographical texts concerning these saints, which are destined for praising the heavenly and also the secular wisdom of the Egyptian church fathers. Such a hagiographical piece is the text of the Berlin ostracon, which first of all speaks about the wisdom of Cyrill, which he possessed even in his childhood. For that reason, the Coptic text is an important evidence of the hagiographical propaganda – literature of the Coptic Monophysites defending the orthodoxy of their church.